Computational Intelligence in Data Science 5th IFIP TC 12 International Conference, ICCIDS 2022, Virtual Event, March 24-26, 2022, Revised Selected Papers - Kalinathan, Lekshmi; R., Priyadharsini; Kanmani, Madheswari; S., Manisha (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed post-conference proceedings of the Fifth IFIP TC 12 International Conference on Computational Intelligence in Data Science, ICCIDS 2022, held virtually, in March 2022. The 28 revised full papers presented were carefully reviewed and selected from 96 submissions. The papers cover topics such as computational intelligence for text analysis; computational intelligence for image and video analysis; blockchain and data science.
Comparative Analysis of Sensor-based Human Activity Recognition using Artificial Intelligence -- A survey on cervical cancer detection and classification using deep learning -- Counting Number of people and social distance detection using deep learning -- Analysis of Age Sage Classification for Students' Social Engagement using REPTree & Random Forest -- Factual Data Protection Procedure on IoT-Based Customized Medicament Innovations -- Deep Learning based Covid-19 patients detection -- A progressive approach of designing and analysis of Solar and wind stations integrated with the grid connected systems -- A Survey on Techniques and Methods of Recommender System -- Live Social Spacing Tracker Based on Domain Detection -- Assessing Layer Normalization with BraTS MRI Data in a Convolution Neural Net -- Data set creation and Empirical analysis for detecting signs of depression from social media postings -- Classification and Prediction of lung cancer with histopathological images using VGG-19 architecture -- Analysis of the Impact of White Box Adversarial Attacks in ResNet While Classifying Retinal Fundus Images -- Factors Influencing the Helpfulness of Online Consumer Reviews -- Perspective Review on Deep Learning Models to Medical Image Segmentation -- Real Time Captioning and Notes Making of Online classes -- Disease Identification in Tomato Leaf using pre-trained ResNet and Deformable Inception -- Allowance of Driving Based on Drowsiness Detection using Audio and Video Processing -- Detection and classification of Groundnut Leaf Disease using Convolutional Neural Network -- Enhanced Residual Connections Method for Low Resolution Images in Rice Plant Disease Classification -- COVI-PROC -- GPS Tracking Traffic Management System using Priority Based Algorithm -- Accident detection system using deep learning -- Monitoring of PV Modules and Hotspot Detection using Convolution Neural Network based Approach -- Literature review on human behavioural analysis using deep learning algorithm -- An improved Ensemble Extreme Learning Machine classifier for detecting diabetic retinopathy in fundus images -- Text Mining Amazon Mobile Phone Reviews: Insight from an Exploratory Data Analysis -- Supervised Learning of Procedures from Tutorial Videos.
Keywords: Data mining; Application software; Artificial intelligence; Image processing-Digital techniques; Computer vision; Computers; Data Mining and Knowledge Discovery; Computer and Information Systems Applications; Artificial Intelligence; Computer Imaging, Vision, Pattern Recognition and Graphics; Computing Milieux; Computer and Information Systems Applications